1994
DOI: 10.1128/mcb.14.7.4373
|View full text |Cite
|
Sign up to set email alerts
|

Elevated frequency of microsatellite mutations in TK6 human lymphoblast clones selected for mutations at the thymidine kinase locus.

Abstract: A major question in carcinogenesis is, How can a normal cell accumulate multiple mutations in different genes on different chromosomes, when the mutation rate of each gene is in the range of 10-8 to The strategy used in the present investigation is to search directly for the existence of second-site mutations in the TK6 human lymphocyte cell line by screening for changes in a number of PCR microsatellite markers located throughout the genome in a set of independent cell clones selected for new mutations at t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0

Year Published

1995
1995
2004
2004

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Additional studies revealed a higher frequency of microsatellite mutations in cells selected for tk mutations than in wild-type cells. 92 However, the same frequency of mutation was recorded in the spontaneously arising tk mutants. In an extensive clonal analysis of hprt mutations grown for 50-60 population doublings, it was found that approximately 25 per cent of the clones showed evidence of chromosomal instability (deletions and translocations).…”
Section: Radiation-induced Delayed Gene Mutations-evidencementioning
confidence: 55%
“…Additional studies revealed a higher frequency of microsatellite mutations in cells selected for tk mutations than in wild-type cells. 92 However, the same frequency of mutation was recorded in the spontaneously arising tk mutants. In an extensive clonal analysis of hprt mutations grown for 50-60 population doublings, it was found that approximately 25 per cent of the clones showed evidence of chromosomal instability (deletions and translocations).…”
Section: Radiation-induced Delayed Gene Mutations-evidencementioning
confidence: 55%
“…Microsatellite instability has also been reported to occur in HNPCC-related tumors other than colon cancer (Risinger et al, 1993;Burks et al, 1994). Moreover, in certain tumor cell lines with micro-satellite instability there is an increased frequency of gene mutation at selectable loci (Bhattacharyya et al, 1994), and it has been suggested that microsatellite instability is associated with a "mutator phenotype" (Li et al, 1994;Loeb, 1994).…”
mentioning
confidence: 99%
“…It is interesting to note that one of the cell lines (SW620) exhibited a low mutation frequency (< 0.37%), which may be comparable to that observed for normal fibroblasts in vitro (Bhattacharyya et al, 1994;Shibata et al, 1994) and T-lymphocytes in vivo (this report). Li et al (1994) studied 12 polymorphic microsatellite markers in 102 independent subclones of the TK6 human lymphoblast cell line. Two mutations were found, corresponding to an in vitro frequency of 0.08% mutations/allele (Table 2).…”
mentioning
confidence: 99%
“…All the various dysgenetic effects (Simons, 1995) in which delayed death, gene mutations and a variety of chromosomal abnormalities can be demonstrated in cells that are not themselves irradiated but are the progeny of cells exposed to ionizing radiation many cell divisions previously have been interpreted as manifestations of a radiationinduced genomic instability ( Figure 1c). Induced instability is a genome-wide process (Li et al, 1992(Li et al, , 1994Grosovsky et al, 1996) and the cellular phenotype is similar to that of the inherited chromosome instability syndromes, characterized by spontaneously high levels of chromosomal abnormalities and mutations (Meyn, 1997;Wright, 1999;Futaki and Liu, 2001). Despite the apparent similarities, radiation-induced genomic instability seems to reflect epigenetic processes rather than mutation of genome maintenance genes (Clutton et al, 1996a;Limoli et al, 1998b;Morgan et al, 2002;Nagar et al, 2003).…”
mentioning
confidence: 99%